Benefits of the destinations, not costs of the journeys, shape partial migration patterns. (15th May 2017) - Yackulic, Charles B.; Blake, Stephen; Bastille‐Rousseau, Guillaume
Summary: The reasons that lead some animals to seasonally migrate, and others to remain in the same area year‐round, are poorly understood. Associations between traits, such as body size, and migration provide clues. For example, larger species and individuals are more likely to migrate. One explanation for this size bias in migration is that larger animals are capable of moving faster (movement hypothesis). However, body size is linked to many other biological processes. For instance, the energetic balances of larger animals are generally more sensitive to variation in food density because of body size effects on foraging and metabolism and this sensitivity could drive migratory decisions (forage hypothesis). Identifying the primary selective forces that drive migration ultimately requires quantifying fitness impacts over the full annual migratory cycle. Here, we develop a full annual migratory cycle model from metabolic and foraging theory to compare the importance of the forage and movement hypotheses. We parameterize the model for Galapagos tortoises, which were recently discovered to be size‐dependent altitudinal migrants. The model predicts phenomena not included in model development including maximum body sizes, the body size at which individuals begin to migrate, and the seasonal timing of migration and these predictions generally agree with available data. Scenarios strongly support the forage hypothesis over the movement hypothesis. Furthermore, male Galapagos tortoises on Santa Cruz Island would be unable to grow to their enormous sizes without access to both highlands and lowlands. Whereas recent research has focused on links between traits and the migratory phases of the migratory cycle, we find that effects of body size on the non‐migratory phases are far more important determinants of the propensity to migrate. Larger animals are more sensitive to changing forage conditions than smaller animals with implications for maintenance of migration and body size in the face of environmental change. Abstract : Among animals that swim or run, larger animals are generally more likely to migrate. Full annual migratory cycle modelling suggests that larger tortoises (and perhaps other large animals) are driven to migrate because their energetic budgets are more sensitive to seasonal changes in vegetation conditions.